IDENTIFIKASI JENIS DAN BERAT KENDARAAN MELALUI JEMBATAN TIMBANG - Samsul Bahri (Universitas Bengkulu, 2019)
This study aimed to identify the type and weight of vehicles that pass roads in Bengkulu through surveys at weigh stations Air Sebakul Bengkulu. The study was conducted because of indications of cargo transport vehicles, exceeding the permitted capacity of roads in Bengkulu Province. The study methods was done byfield survey. The results showed that 98.71% of vehicles that pass through weigh stations Air Sebakul Bengkulu is a type of vehicle two aces. 95% of heavy vehicles passing through roads in Bengkulu exceed the heaviest load axis (MTS), which allowed when applying zero tonnage and 77% of vehicles exceeding the permitted MTS when applying the tolerance to 50%.